Australia : IOSCO Objectives and Principles of Securities Regulation-Detailed Assessment of Implementation. (IMF Staff Country Reports; Country Report ;, 2012)
The Australian legal and regulatory framework for securities markets exhibits a high level of compliance with the International Organization of Securities Commissions (IOSCO) Principles. A few remaining concerns need to be resolved, including some identified in the 2006 assessment. Australian Securities and Investments Commission's (ASIC) operational independence and sufficiency of resources are overarching concerns which impair its ability to discharge its supervisory functions adequately and effectively across the entire regulated population.